Service quality and customer satisfaction: qualitative research implications for luxury hotels. Issue 2 (1st June 2015) - Lu, Carol; Berchoux, Celine; Marek, Michael W.; Chen, Brendan
Abstract : Purpose: – The purpose of this paper was to determine whether luxury hotel managers and customers have the same understanding of service quality and satisfaction and whether there is a disparity between services offered by luxury hotels and the way customers actually experience them. Design/methodology/approach: – This paper used interviews with managers and guests of 5-Star hotels in Taiwan and qualitative analysis to understand definitions and perceptions of luxury, service quality and satisfaction. Findings: – The major findings of the study were that: there were no fundamental disconnects in the respective understandings of managers and guests; however, the two groups used different language to describe luxury, service quality and satisfaction; the managers evaluated satisfaction in terms of services provided, but the guests conceptualized satisfaction in terms of value received for the price of lodging; and luxury, service quality and satisfaction were closely related in the minds of the managers and guests and were not independent constructs. Research limitations/implications: – Recommendations are made based on marketing communications theory, that is all factors identified in this study can be considered to be part of the brand identity of the hotel; local culture can introduce variables that may be outside the scope of international standards; and information on local expectations and preferences can inform advertising and public relations efforts of the hotel. Originality/value: – This study is significant because little research into luxury hotel customer satisfaction has been done using qualitative methodology, which provides a richer understanding of the experiences of the participants than can quantitative design.